Three techniques of ski jump take-off modeled by changes of joint angle - Sasaki, T.; Tsunoda, K.; Hoshino, H. (1998)
INTRODUCTION: In ski jumping, take-off action is the most important factor for ascent force. Jumpers should aim for optimum movements of the joints, because reaction force is the result of the integrated kinetic parameters of each joint or segment. In our recent studies, three techniques of take-off action were classified by manner of joint power generation. However, such kinetic parameters are difficult to explain in coaching situations. It would be more useful for coaching to represent the three techniques of take-off action by joint angle rather than joint power. The purpose of this study is to establish visual models of ski jump take-off action of world class jumpers based on changes of joint angle which would be especially useful in coaching.